Cost of transport, but not gluteus medius and red blood cells monocarboxylate-transporters density differentiated Brazilian Sport Horses at two performance levels. (March 2022) - Feringer-Júnior, Walter Heinz; de Carvalho, Júlia Ribeiro Garcia; Moranza, Henriette Gellert; de Almeida, Maria Luiza Mendes; Lemos, Eliana Gertrudes Macedo; Soares, Otávio Augusto Brioschi; Ribeiro, Gesiane; de Camargo Ferraz, Guilherme
Abstract: Cost of transport (COT) and monocarboxylate transporters (MCTs) could affect the ability to perform fast actions during a jumping discipline. This study aimed to compare the COT and evaluate the MCT1, MCT4, and their auxiliary protein CD147 content in the gluteus medius and RBCs of Brazilian sport horses (BH), a breed developed for jumping competitions, with low-level (LL) or intermediate-level (IL) jumping capacities. The physiological difference between the horses was assessed by an incremental jump test (IJT), in which the cost of lactate (COTLAC ) and heart rate (COTHR ) of running were determined for each animal by the ratio between each variable and the running speed. Western blotting was performed on muscle and RBC membranes to quantify MCT1, MCT4, and CD147. IL showed lower COTLAC and COTHR than LL at all jumping heights. The amount of MCT1, MCT4, and CD147 found in muscle and RBCs were not dependent on performance level. Muscle MCT4 and MCT1 were correlated positively with CD147. We conclude that the relatively small differences between performances did not relevantly influence MCT expression in BH. While MCT analyses are inaccessible for most trainers and veterinarians, the cost of transport measurements is a feasible and sensitive tool to distinguish intermediate and low-level jumping horses. Highlights: Monocarboxylate-transporter (MCT) density may not alter the ability to perform jumping sports. MCTs were found at considerable amounts in the BH horses erythrocytes and muscle. Positive relationship was found between the CD147 and MCT1 and MCT4 in muscle. Small difference between performance level has no relevance in MCT density in BH horses.